The Effects of Mid-life Stress Exposure on Black-White Differences in Cognitive Decline. (17th December 2021) - Mitchell, Uchechi
Abstract: Cognitive decline is a precursor to cognitive impairment and dementia. Recent research suggests that cognitive decline may begin earlier in the life course for Blacks and that Black-white disparities in cognitive function emerge in midlife. Disproportionate exposure to chronic and acute stressors during mid-life may explain Black-white differences in trajectories of cognitive function over time. In this study we use data from approximately 3, 700 Black and white respondents age 51-64 from the Health and Retirement Study to examine race differences in cognitive decline and the role mid-life stress exposure play in these differences. Initial findings suggest that mid-life Blacks have lower levels of cognitive function, but their rates of cognitive decline do not differ significantly from mid-life whites. Financial strain and everyday experiences of discrimination are inversely associated with cognitive decline and only partially explain differences in cognitive decline between mid-life Blacks and whites.